Conditional Knockouts of Interphotoreceptor Retinoid Binding Protein Suggest Two Independent Mechanisms for Retinal Degeneration and Myopia - Getz, Tatiana E; Chrenek, Micah A; Papania, Jack T; Shelton, Debresha A; Markand, Shanu; Iuvone, P Michael; Kozmik, Zbynek; Boatright, Jeffrey H; Nickerson, John M (Investigative ophthalmology & visual science, 2024)
PURPOSE: Interphotoreceptor retinoid-binding protein's (IRBP) role in eye growth and its involvement in cell homeostasis remain poorly understood. One hypothesis proposes early conditional deletion of the IRBP gene could lead to a myopic response with retinal degeneration, whereas late conditional deletion (after eye size is determined) could cause retinal degeneration without myopia. Here, we sought to understand if prior myopia was required for subsequent retinal degeneration in the absence of IRBP. This study investigates if any cell type or developmental stage is more important in myopia or retinal degeneration. METHODS: IBRPfl/fl mice were bred with 5 Cre-driver lines: HRGP-Cre, Chx10-Cre, Rho-iCre75, HRGP-Cre Rho-iCre75, and Rx-Cre. Mice were analyzed for IRBP gene expression through digital droplet PCR (ddPCR). Young adult (P30) mice were tested for retinal degeneration and morphology using spectral-domain optical coherence tomography (SD-OCT) and hematoxylin and eosin (H&E) staining. Function was analyzed using electroretinograms (ERGs). Eye sizes and axial lengths were compared through external eye measurements and whole eye biometry. RESULTS: Across all outcome measures, when bred to IRBPfl/fl, HRGP-Cre and Chx10-Cre lines showed no differences from IRBPfl/fl alone. With the Rho-iCre75 line, small but significant reductions were seen in retinal thickness with SD-OCT imaging and postmortem H&E staining without increased axial length. Both the HRGP-Cre+Rho-iCre75 and the Rx-Cre lines showed significant decreases in retinal thickness and outer nuclear layer cell counts. Using external eye measurements and SD-OCT imaging, both lines showed an increase in eye size. Finally, function in both lines was roughly halved across scotopic, photopic, and flicker ERGs. CONCLUSIONS: Our studies support hypotheses that for both eye size determination and retinal homeostasis, there are two critical timing windows when IRBP must be expressed in rods or cones to prevent myopia (P7-P12) and degeneration (P21 and later). The rod-specific IRBP knockout (Rho-iCre75) showed significant retinal functional losses without myopia, indicating that the two phenotypes are independent. IRBP is needed for early development of photoreceptors and eye size, whereas Rho-iCre75 IRBPfl/fl knockout results in retinal degeneration without myopia.
Keywords: Animals; myopie; Tomography, Optical Coherence; Female; elektroretinografie; Retina; ženské pohlaví; Mice, Knockout; proteiny vázající retinol; myši knockoutované; optická koherentní tomografie; Mice; degenerace retiny; myši; Eye Proteins; oční proteiny; Male; modely nemocí na zvířatech; Disease Models, Animal; retina; Myopia; zvířata; mužské pohlaví; Mice, Inbred C57BL; Retinol-Binding Proteins; Retinal Degeneration; Electroretinography; myši inbrední C57BL